(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
Although uncommon, hypersensitivity( allergy) and idiosyncratic reactions are potentially disastrous without early recognition and effective management. A 16 years old male patient suffering from stricture urethra (post traumatic) scheduled for urethro plasty under SAB(Subarachnoid block). But during preloading with intravenous fluid patient suddenly developed dyspnea, wheezing and rash which was managed immediately with steroid , antihistamine and bronchodilator and diagnosed as febrile reaction and surgery posponded. After 6 months he was again scheduled for surgery and at that time no adverse reaction was revealed after IV infusion for 15 minutes but suddenly developed severe respiratory distress and cardiac arrest and diagnosed as anaphylactic reaction which was managed with inj. adrenaline, cardiac massage, intubation & ventilation with 100% O2. And patient became completely stable within minute. Journal of BSA, Vol. 20, No. 1, January 2007 p.34-35